Cuca fresca: um jogo da memória adaptável para crianças com deficiência - CARVALHO, Caio Pinheiro de (2019)
Educational Technology is an area of knowledge that proposes the use of technologies as part of the pedagogical project of knowledge construction. In this context, digital games can be integrated into the educational process, allowing children to experience playful moments as part of learning. However, children with disabilities or reduced mobility have difficulties because most educational applications available in the market presents little or no customization option for the social inclusion of this public. Keeping this in mind, Cuca Fresca was developed, an adaptable memory game allowing customizable configurations such as theme creation, color adjustment, timer setting, and other parameters. This work describes the game implementation process, along with the tools used. Usability tests and data collection were performed with health professionals specialized in the care of children with disabilities. Also, feasibility tests were performed to verify the behavior of the game with a non-conventional interaction (head tracking). The results indicate a great acceptance of the idea of personalizing forms of interaction for children who need specialized and personalized attention.